The Recherla Reddy’s Temples of Pillalamarri (Suryapet District) - Barigala, Narasaiah (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Recherla Reddy’s were born in ‘Manuma Caste’. They are native of amanagallu.  The progenitor of Recherla family is a Brahma Senani. These rulers were famous as Recherla’s of Pillalamarri. This village 5 km from Suryapet District.  In Pillalamarri there are 3 famous Temples built by Recherla Reddys’. There are seven inscriptions also available about these temples.• The Trikuta Temple• Nameswara Temple• Erakeswara Temple
Keywords: Manuma caste; Pillalamarri Temples; Recherla Reddy’s